INTERAKSI SOSIAL PEREMPUAN MUSLIM BERCADAR - Ahmad Yusron; Khalasa Shafira; Uun Machsunah; Ida Ri'aeni (JIKE: Jurnal Ilmu Komunikasi Efek, 2020)
This study aims to determine the social interaction that occurs in veiledMuslim women in the Ummahat Community with the surrounding environmentand to see how the communication behavior of veiled women interacts with thesurrounding environment.This research uses descriptive qualitative method with the informanttechnique using purposive sampling technique. Data collection techniques carriedout by observation, interviews, and documentation. As for data analysis using theinteractive analysis model of Miles and Hubberman.Keywords: Social Interaction, Communication Behavior, Symbolic InteractionTheory, Veils.